Always put in a recipe and other tips for living from Iowa's best known homemaker - Birkby, Evelyn (Bur oak book., 2012)
In 1949, Iowa farm wife Evelyn Birkby began to write a weekly column entitled "Up a Country Lane" for the Shenandoah Evening Sentinel, now called the Valley News. Sixty-three years, one Royal typewriter, and five computers later, she is still creating a weekly record of the lives and interests of her family, friends, and neighbors. Her perceptive, closely observed columns provide a multigenerational biography of rural and small-town life in the Midwest over decades of change. Now she has sifted through thousands of columns to give us her favorites, guaranteed to delight